2012
DOI: 10.1021/jp208191c
|View full text |Cite
|
Sign up to set email alerts
|

Dispersant Effects in the Selective Reaction of Aryl Diazonium Salts with Single-Walled Carbon Nanotubes in Aqueous Solution

Abstract: Current methods of synthesis for carbon nanotubes (CNTs) usually produce heterogeneous mixtures of different nanotube diameters and thus a mixture of electronic properties. Consequently, many techniques to sort nanotubes according to their electronic type have been devised. One such method involves the chemical reaction of CNTs with aryl diazonium salts. Here we examine the reactions of electric arc produced CNTs (dispersed by a variety of surfactants and polymers in aqueous solution) with 4-bromo-, 4-nitro-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 63 publications
2
49
0
Order By: Relevance
“…Raising the pH of the solution is able to deprotonate the surface oxides, thus recovering the nanotubes' optical properties. This behaviour is known to occur in SDS-based suspensions [28], as well as for DNA [29,30] and poly(maleic acid/octyl vinyl ether) [16], however it does not appear to occur in dispersion of CNTs with many other surfactants [31], at least not to the same extent. This is most likely due to the density of the adsorbed surfactant layer and the corresponding ability of that layer to exclude oxygen from the nanotube surface [29].…”
Section: Resultsmentioning
confidence: 94%
“…Raising the pH of the solution is able to deprotonate the surface oxides, thus recovering the nanotubes' optical properties. This behaviour is known to occur in SDS-based suspensions [28], as well as for DNA [29,30] and poly(maleic acid/octyl vinyl ether) [16], however it does not appear to occur in dispersion of CNTs with many other surfactants [31], at least not to the same extent. This is most likely due to the density of the adsorbed surfactant layer and the corresponding ability of that layer to exclude oxygen from the nanotube surface [29].…”
Section: Resultsmentioning
confidence: 94%
“…18,25 In cases where the dispersant forms a wrapping layer that provides a sufficient barrier to oxygen, the optical properties of the CNTs are greatly enhanced. 26 It is suggested that the lability and loose organization of SDS molecules on the nanotube surface allows for such oxidation to take place.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ideally, the best dispersion is achieved when all the SWCNTs are individualized and isolated. Different aqueous solutions including ionic, non-ionic, biological and polymeric surfactants have been probed as the liquid media for SWCNT dispersion [6][7][8]. Among them, SDBS has been widely used in the past and it is still considered as a quite efficient medium for dispersing SWCNTs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other important SWCNT features can be studied from absorption spectra, including the influence of covalent functionalization on the electronic properties [6]. On the other hand, exfoliation of aggregates and bundles of a given SWCNT powder material during ultrasound treatments in a liquid dispersion medium can be monitored through absorption spectroscopy, and the maximum achievable exfoliation coincides with the maximum absorbance [13].…”
Section: Introductionmentioning
confidence: 99%